Banking and finance in Bangladesh : a collection of essays - Hassan, Kabir (Dhaka : Academic Publishers, 1995)
Business
Keywords: Banking; Finance; Econometric analysis; Black market; Economic development; Financial development; Income; Monetary policy; Macroeconomics; Commercial bank; Public industries